EFEKTIVITAS MEDIA POWER POINT PADA KETERAMPILAN MENYIMAK BAHASA ARAB KELAS VII DI MTs N 2 KUDUS: THE EFFECTIVENESS OF POWER POINT MEDIA ON CLASS VII ARABIC LISTENING SKILLS AT MTs N 2 KUDUS - Andarista, Luthifah; Zukhaira; Multazam (Universitas Negeri Semarang, 2024)
Mastery of vocabulary, especially Arabic listening skills, is a basic ability that students must master in order to learn Arabic. Vocabulary mastery in listening skills in class VII MTs N 2 Kudus is still relatively low. Student enthusiasm and activity are still quite lacking due to several factors. Apart from that, there is a lack of media use by teachers. So students seem monotonous when learning Arabic in class. Therefore, there is a need for interactive media so that it can attract students interest in learning Arabic. One of them is by applying interactive power pointmedia to improve vocabulary mastery in Arabic listening skills for class VII MTs N2 Kudus. The type and design of this research are quantitative and quasiexperimental, with a pre-test-post-test nonequivalent control group design pattern.Data collection techniques use tests and non-tests. The data analysis technique is hypothesis testing. The research results show that the implementation of the use of interactive power points in learning activities to master vocabulary and Arabic listening skills in class VII MTs N 2 Kudus is quite effective. This is proven based on the test results, namely that in the control class, the average pre-test score was 64.25 and the average post-test score was 70.77. The experimental class had an average pre-test score of 66.19 and an average post-test score of 85.50. From the t-test calculation using SPSS, the t-calculated value for the experimental class obtained a significance value for the pre-test and post-test for the experimental class of 0.000, which means (sig < 0.05). This proves that there is an increase in the average of the pre-test and post-test results of the experimental class. This proves that there is an influence of Power Point media on the post-test results of the experimental class. So there was a rejection of Ho, and what was accepted was Ha, namely that the use of power point media was effective in mastering vocabulary in Arabic listening skills in class VII MTs N 2 Kudus.